Development of safe semi-automatic and economic blood cross matching using image processing. (2021) - Jayakumar, P.; Padmanabhan, S.; Suthendran, K.; Rajveer, G.V.
Abstract: Naming the Blood group is an imperative test for blood transfer and innumerable medical intervention. Generally, the medical practitioner confirms blood typing and its cross-matching suitability before transferring the blood from a person to another. Crossmatch is a fundamental test and is required for wherever blood transfer is needed. While handling an accident case or some emergency, the technicians are performing this test in an open environment which may affect the process and sometimes harmful for technicians. In many hospitals and laboratories, these kinds of tests are carried out in manual using micro plate and test tube. It is time-consuming, error-prone and sometimes it ends up with disease infection for laboratory technicians. Moreover, there is no possibility to revisit the same test results because once after marking it they clean the entire test outcomes. To mitigate the above issues, we propose to design and develop semi-automatic and economical blood cross-matching identification device. This device provides the cross-matching results based on the bonding and its image morphology of the captured image. Further, it provides a captured image for further reference.